Analysis of the Performance of Straight Bevel Gear and Zero Degree Spiral Bevel Gear for an Engine based on Dynamic Transmission Error - Liu Yang; Tang Jinyuan; Bai Fan (Jixie chuandong)
For the practical engineering problems,the dynamic transmission error measurement of a two-stage cylindrical gear-bevel gear high-speed transmission system with a straight bevel gear pair and a zero degree spiral bevel gear pair is carried out based on the test method. The measured dynamic transmission error data are filtered,and the dynamic performance parameters of high speed bevel gear are obtained with filter analysis. The results show that: When using zero-degree spiral bevel gear,the low-frequency of its dynamic transmission error is much lower than that of the straight bevel gear. And with the use of zero degree spiral bevel gear,the amplitude of high-frequency of its dynamic transmission error is much larger than the amplitude of that of the straight bevel gear. The high frequency band determines the dynamic characteristics of the transmission system. Therefore,it can be concluded that when using zero degree spiral bevel gears,the dynamic performance of the system will be inferior to that of straight bevel gear.